External proficiency testing for histocompatibility and immunogenetics in today and future - Oguz, Fatma Savran (Frontiers in Genetics, 2024)
The Histocompatibility and Immunogenetics laboratories provide disease association and pharmacogenetic analyses as well as the tests required for transplantation immunology and transfusion medicine. They perform Human Leukocyte Antigen (HLA) genotyping in patients/recipients and potential donor candidates for solid organ and stem cell transplants using various molecular methods, and determine mismatches. In addition, they also perform HLA antibody tests to detect anti-HLA antibodies in patients and flow cross-matches to evaluate donor-recipient compatibility. Evidence-based clinical guidelines have emphasized the importance of laboratory tests in clinical practices for a long time. Understanding the principles of Quality Control and External Quality Assurance is a fundamental requirement for the effective management of Tissue Typing laboratories. When these processes are effectively implemented, errors in routine assays for transplantation are reduced and quality is improved. In this review, the importance of Quality Assurance, Quality control and proficiency testing in Histocompatibility and Immunogenetic testing, the necessity of external proficiency testing (EPT) for accreditation, and existing and potential EPT programmes will be reviewed and evaluated in the light of the literature.